Nonlinear flow-induced vibration response characteristics of leaching tubing in salt cavern underground gas storage. (September 2021) - Liu, Jun; Zeng, Linlin; Guo, Xiaoqiang; Dai, Liming; Huang, Xiao; Cai, Ling
Highlights: A nonlinear flow-induced vibration model of leaching tubing in salt cavern gas storage was established. Nonlinear factors such as the longitudinal and lateral coupling effect, contact/collision between the center tube and middle tube were considered. The influences of the water injection flow rate, two-port distance, and tubing diameter on the vibration response characteristics of leaching tubing were analyzed systematically. The research results provide a theoretically sound guidance for designing of leaching tubing in salt cavern gas storage. Abstract: To address flow-induced vibration failure problems of leaching tubing in salt cavern underground gas storage, a nonlinear flow-induced vibration model of the leaching tubing in salt cavern gas storage was established using the energy method, element method, and Hamilton variational principle. In the model, nonlinear factors such as the longitudinal and lateral coupling effect and contact/collision between the center tube and middle tube (tube in tube) were considered. Based on the on-site M example well parameters in Jianghan Oilfield, an experiment to simulate leaching tubing vibration was designed using the similarity principle and carried out to verify the validity and correctness of the proposed model. Thus, the effects of the water injection flow rate, two-port distance, and tubing diameter on the vibration response characteristics of the leaching tubing were analyzed systematically. The vibration failure mechanism of the leaching tubing was revealed, and vibration control methods of the leaching tubing were proposed. First, with the increase in water injection flow rate, the lateral displacement and bending stress of the lower end of the leaching tubing increase, and when the injection flow rate was 50–70 m 3 /h, the vibration intensity of string increased significantly; therefore, the on-site water injection flow rate should be avoided using this interval operation. Second, with the increase in the two-port distance, the vibration response of the center tube increased; when the two-port distance was greater than 40 m, the vibration amplitude and energy of the tubing string increased significantly, and thus the two-port distance should be less than 40 m to the greatest extent possible in on-site production. Third, when the diameter of the leaching tubing decreased, the vibration amplitude and frequency increased, and the corresponding probability of bending deformation and fatigue failure increased significantly; therefore, provided that the other conditions are met, selecting a large tubing string can effectively improve the safety of the leaching tubing string.